SYNTHESIS, CHARACTERIZATION AND EVALUATION OF NOVEL QUINOLINE MOLECULES AS ANTIBACTERIAL AGENTS - SEEMA KHAN; NARENDRA K. SINGH; SHANKAR SINGH; AVINASH K. KONDALKAR (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The objective of the present investigation was to synthesize novel quinoline derivatives for antibacterial activity. Five compounds SK1-5 were synthesized and these compounds were tested yield (%), solubility, retention factor (Rf) and melting point (°C). The compounds were evaluated for antibacterial activity using zone of inhibition method at four different concentrations. The products were insoluble in water, methanol and DMSO while they were soluble in chloroform and were obtained in 67 - 76 % yield. The antibacterial action against both gram-positive and gram-negative bacteria was exhibited by the compounds. The compounds were found to be possessing better inhibitory action against the gram-negative bacteria in comparison to gram positive bacteria. The zone of inhibition exhibited by SK3 was highest among all compound and it was equally effective in both gram-negative and positive bacteria.